1994
DOI: 10.1093/jnci/86.12.913
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Modulation of Steady-State mdr Gene Expression and Drug Resistance in Murine Colon Cancer Cells

Abstract: Results of this study have demonstrated that the in vivo sensitivity of murine CT-26 colon carcinoma cells to doxorubicin depends on the organ environment. The organ environment can influence the P-glycoprotein-mediated multidrug-resistant phenotype in tumor cells, and the increased expression of P-glycoprotein is transient; once removed from the environment (lung), the cell's resistance reverts to that of the sensitive parent cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 0 publications
2
48
0
1
Order By: Relevance
“…In these models, tumour cells are selected in vitro for the MDR phenotype by exposure to anticancer drugs and then injected subcutaneously in the back or flank of nude mice. Although these models are adequate for specific assays, such as the rapid screening of new compounds, they cannot reproduce the physiological environment, which Results are expressed as mean ± SD of at least four mice MIBI 99m Tc-sestamibi, t 1/2 washout half-time, WR (%) percentage washout rate, T/NT 5 min tumour/non-tumour ratio at 5 min, T/NT 60 min tumour/ non-tumour ratio at 60 min *p<0.05 compared with 143B-luc + tumours without PSC833 **p<0.05 compared with MNNG/HOS-luc + tumours without PSC833 [45] demonstrated that the organ environment influences the Pgp expression in colon carcinoma cells, affecting their in vivo sensitivity to doxorubicin. The Pgp gene expression depends on a variety of host factors such as interaction with the extracellular matrix and environmental mitogenic signals [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In these models, tumour cells are selected in vitro for the MDR phenotype by exposure to anticancer drugs and then injected subcutaneously in the back or flank of nude mice. Although these models are adequate for specific assays, such as the rapid screening of new compounds, they cannot reproduce the physiological environment, which Results are expressed as mean ± SD of at least four mice MIBI 99m Tc-sestamibi, t 1/2 washout half-time, WR (%) percentage washout rate, T/NT 5 min tumour/non-tumour ratio at 5 min, T/NT 60 min tumour/ non-tumour ratio at 60 min *p<0.05 compared with 143B-luc + tumours without PSC833 **p<0.05 compared with MNNG/HOS-luc + tumours without PSC833 [45] demonstrated that the organ environment influences the Pgp expression in colon carcinoma cells, affecting their in vivo sensitivity to doxorubicin. The Pgp gene expression depends on a variety of host factors such as interaction with the extracellular matrix and environmental mitogenic signals [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…siRNA has become a potential alternative for treating multi-drug resistant metastasis, which is the major cause of death in cancer patients [1]. Selective delivery of siRNA to metastatic tumors remains a major obstacle for siRNA based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that the effect of antimetastatic agents can be differentially modulated by organ microenvironments, 21,22) because of, in part, a different host cell population and different pharmacokinetics. Therefore, it is important to explore whether MS-209 reverses the MDR of metastatic SCLC cells in various organs.…”
Section: Discussionmentioning
confidence: 99%